Research of Working Process of a Vibration Machine with Controlled Parameters of Motion - Nazarenko, Ivan; Dedov, Oleg; Ruchynskyi, Mykola; Sviderskyi, Anatoly (International Journal of Engineering and Technology, 2018)
The constructive scheme of the vibration unit is developed. Presented results of researches of a rammers on determination of parameters, which will provide high efficiency of vibration action on the processed environment for ensuring the quality of the compaction process, which is based on the idea of direct transfer of energy from the working organ to the processed environment. Revealed zones of effective operation of the parameters and characteristics of the system "machine-environment" to ensure high quality of the compaction process, which is based on the idea of the purposeful use of elastic characteristics of the general vibration system, which, under all the same conditions, also reduces the energy costs for some machines to 50%.Â Â